2022
DOI: 10.3390/ijerph19159647
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Screening Practices and Perceived Barriers to Offering Tobacco Cessation Services among Texas Health Care Centers Providing Behavioral Health Treatment

Abstract: Tobacco use, and thus tobacco-related morbidity, is elevated amongst patients with behavioral health treatment needs. Consequently, it is important that centers providing health care to this group mandate providers’ use of tobacco screenings to inform the need for tobacco use disorder intervention. This study examined the prevalence of mandated tobacco screenings in 80 centers providing health care to Texans with behavioral health needs, examined key factors that could enhance screening conduct, and delineated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…In our sample of SUTCs, only about 39% of providers had received tobacco training in the year prior to program implementation; this number almost doubled by post-implementation. Low pre-implementation training receipt rates are consistent with those reported within prior studies in healthcare settings [63] and in SUTCs in particular [29]. However, consistent with expectations of the outcomes of increased training receipt, there were significant increases in provider beliefs that it was as critical to treat tobacco use as it was to treat other substance use throughout treatment and in provider self-efficacy to deliver TUAs effectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In our sample of SUTCs, only about 39% of providers had received tobacco training in the year prior to program implementation; this number almost doubled by post-implementation. Low pre-implementation training receipt rates are consistent with those reported within prior studies in healthcare settings [63] and in SUTCs in particular [29]. However, consistent with expectations of the outcomes of increased training receipt, there were significant increases in provider beliefs that it was as critical to treat tobacco use as it was to treat other substance use throughout treatment and in provider self-efficacy to deliver TUAs effectively.…”
Section: Discussionsupporting
confidence: 81%
“…However, tobacco use screenings, a natural first step prior to the delivery of evidence-based interventions, are not pervasive within SUTCs. A recent Texas-based study published in 2022 indicated that 80% of participating SUTCs mandated tobacco use screenings, an increase from 70.2% recorded in a 2016 study, though samples may have differed between studies [29,30]. While these statistics potentially indicate an improvement in SUTC tobacco screening delivery over time, sizeable gaps in screening practice still exist with the growing spectrum of tobacco products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providers in substance use treatment centers commonly report several barriers to screening and intervention in patients' smoking, including, but not limited to, a lack of time and training [22][23][24][25][26][27][28][29][30]. The current study found that substance use treatment centers with more provider-reported barriers to routine smoking cessation intervention delivery at preimplementation experienced greater gains in assessing patients' interest in quitting smoking.…”
Section: Discussionmentioning
confidence: 84%
“…For example, providers may be concerned that addressing their patients' smoking may interfere with their nonnicotine substance use recovery [21]. Additionally, a variety of other barriers exist, including a lack of knowledge and training in treating tobacco dependence (i.e., low self-efficacy), inadequate time and resources, and the high rates of smoking among the providers themselves [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%